Enhanced Routing Model for Wireless Sensor Networks in Precision Agriculture for Communicating the Soil Moisture - M. Rajeshkumar, Dr. B. Sureshkumar (International Journal of Advanced Science and Technology, 2020)
Monitoring the soil moisture by and large done by manual perception of specialists in agriculture territory. It is clearly require some investment, particularly when monitoring the declining level of soil moisture. This training is less effective particularly while inspecting the degree of soil moisture contained plants in it. For that we need an answer for improve productivity as far as utilization of time and regarding encouraging the monitoring of soil moisture conditions. Our proposed system to screen soil moisture utilizes Libmium Waspmote as a microcontroller. The way toward sending information from the sensor to the Internet network and afterward to the data set worker took around 10-15 seconds. As of late, the expanding request on natural cultivating requires persistent monitoring of plant wellbeing. So as to guarantee the quality and quantity this turns out to be more basic. Consequently, the target of this examination is to build up a remote monitoring system that consistently screens the soil moisture of the plant. The Wireless Sensor Network (WSN) is coordinated with Internet of Things (IoT) to accomplish the above goal. Further, to upgrade the network lifetime, this was impacted by the way toward taking information from the load up and furthermore the defer when the sensor associated with the accessible network. The consequences of system testing demonstrated that the system can work as it were on the off chance that scientists leave the soil with high stickiness, at that point analysts need to screen soil moisture at a specific moisture level, at that point the specialists basically set the degree of moistness that needs to be kept up by the application system. In the event that the soil moisture content is equivalent or not exactly the point set on the system, the system gave warning right away. The process of identifying the routes and managing the traffic in WSN Plays the major role in the research.